Evaluasi Termal Vertical Greenery System Tipe Green Facade pada Dinding Bangunan - Muhammad Haviz; Muhammad Taufik Toha; Riman Sipahutar; Oki Alfernando (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
Increasing of ambient temperature due to global warming has a direct impact on increasing the room temperature. Heat from surrounding is transferred to building wall and room. By installing the Vertical Greenery System (VGS) on the building wall, it can be an alternative for heat absorber and eco-friendly indicator. The aims of this study are to determine the temperature that can be reduced by VGS type Green Façade (GF) and  achieve the energy consumption reduction because of GF installation.  GF is installed on the building wall, property of Mining Engineering Department, Sriwijaya University, to measure its temperature, then compare it with the  temperature on control wall. The results showed that the GF can reduce the room temperature up to 1,2oC, compared to the control wall and the average is 0,3oC. The decrease in average temperature causes a decrease in energy consumption due to the use of air conditioners by 1.56-1.92%. Keywords: global warming, green facade, thermal evaluation, vertical greenery system